Soeman Hs as a Leading Lead of Education in Pekanbaru, Riau 1954-1963 - Merri Natalia; Umasi Umasi; Corry Iriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study, entitled "Soeman Hs as an Educational Motivator in Pekanbaru, Riau in 1954-1963" raises the issue of how Soeman Hs' role in contributing and contributing to the advancement of Education in Pekanbaru, Riau deserves an award, but there is no complete biography about him. This study aims to determine the background of life, role in education and the works of Soeman Hs. The method used is historiography method with a qualitative approach, while the data collection techniques are observation, interviews and documentation. Based on the research, the following results were obtained: Soeman Hs is a teacher who writes various works in the form of novels. Soeman was the driving force behind the establishment of the first junior high school and university in Pekanbaru, Riau. Soeman's family life is a noble family, his father is a descendant of the Mandailing kingdom, because there was a struggle for the throne which left Wahid disappointed, Soeman's father caused Wahid to leave the Mandailing land and choose Bengkalis, Riau as a place to stop and start a new life as a farmer and teacher of the Koran. Because Soeman's father often met merchants for copra buying and selling transactions, Soeman also often interacted with merchants who would make Soeman aware of the different conditions that existed at home and abroad. Soeman aspires to be a teacher to educate the nation's life. For Soeman intelligence will be able to create a national movement. Soeman Hs has received many awards from the novels written, even Soeman Hs is called the father of education in Pekanbaru, due to his simplicity and pattern of thinking that always encourages young people who are not in school to take education to a higher level.